Arranjos urbanos e subjetivos contemporâneos na invenção de territórios turísticos - Alverga, Alex Reinecke de (2011)
We seek consistency empirical and analytical rigor to the concept of touristification in the course of the contemporary arrangements of subjectivity and urbanity stations through a landscape of social (dis)encounters between residents and foreigners living in the capital of Rio Grande do Norte, Natal. In the last three decades the city has become a major destination country for national and international tourism, making tourism an important monitor of choreography in search of synchrony between cities and subjectivities, orchestrated by the cyclical crises and the relentless battle for systemic capitalistic expansion and survival. We proceed with an ethnographic and cartographic inspiration in Ponta Negra, where the waterfront redevelopment in 2000 conducted by the government, influenced the implementation of various establishments, services and practices related to the construction of Natal s major industry hub of tourism and entertainment. We proposed an arch-genealogy of touristification inspared on Michel Foucault analytical perspective, increased by authors in confluence or in different theoretical and methodological approaches, among which stand out Karl Marx, Gilles Deleuze and Felix Guattari, Michael Hardt and Antonio Negri. The reflections that initially turned to the advancement of the sphere of consumerism as the issue capable of articulating the developmental trajectory of the capitalist system and the practice of tourism, promoting some effects (un)desirable in the conflictual dynamics of the condition of the district of Ponta Negra, territory each again (re) produces the designs to meet the consumption by affluent portion of the population and foreign, encountering social exclusion and inclusion differentiated a growing trend. We go forward with an analysis of the "liberation of desire" phenomenal features of the process of producing subjective, providing a breakdown of the recent world s financial crisis initially, but proved social and political crisis also, through a plot derived from the operation of real estate speculation, which Natal is mainly caught through touristification, showing the outlines of a generalized crisis in establishing a new order buoyed by the emergence of a context "biopolitical" since it is a major route that uses the capital to survive and expand, while guiding the process of "strategic beautification" held in Ponta Negra, problematized by us. We conclude by assessing the appropriateness of proposing on further analysis to explore the establishment of a "new social ontology in terms of interference touristification ongoing and the constitution of a "new order" local/global, away from that characterize a system's capitalist overcoming, try to give emphasis in the current stage of the radicalization of a capitalistic utopia